Taking the Brakes Off Targeted Protein Degradation. Issue 1 (16th January 2020) - Kozicka, Zuzanna; Petzold, Georg; Thomä, Nicolas H.
Abstract : PCSK9 heightens LDL cholesterol levels by chaperoning the liver LDL receptor to lysosomes for degradation. In this issue of Cell Chemical Biology, Petrilli et al. (2020) identify novel PCSK9 ligands and convert them into a proof-of-concept degrader, offering a unique way to modulate this key protein-protein interaction. Abstract : PCSK9 heightens LDL cholesterol levels by chaperoning the liver LDL receptor to lysosomes for degradation. In this issue of Cell Chemical Biology, Petrilli et al. (2020) identify novel PCSK9 ligands and convert them into a proof-of-concept degrader, offering a unique way to modulate this key protein-protein interaction.